Penatalaksanaan Fisioterapi Pasca Operasi Pemasangan Plate And Screws Fraktur Clavicula Dextra 1/3 Distal Di Rsud Panembahan Senopati Bantul - Rillo Pambudhi, Risky; , Sugiono, S.Fis.MH.Kes (2015)
Background: Fracture is a fracture in the continuity of the bone structure in the form of cracks, crease or complete with a bone fragment bergeser.fraktur usually also accompanied by complications such as edema, spasm, tenderness, motion and silence, as well as the limited space around the bone joints Clavicula. Aim of research: to know the implementation of physiotherapy in reducing pain, spasm, maintain range of motion, accelerating bone repair and maintain muscle quality in case of fracture Clavicula dektra using infra red rays and the modalities of exercise therapy (passive exercise, active exercise and hold relax). Results: after treatment for 6 times showed dektra shoulder pain assessment, nyer press T0: 4.3 to T6: 2.2, silent pain T0: 2.2 to T6: 0. The motion pain T0: 7.4 into a T6 : 4.6, increased range of motion is active when T0: S: 30o-0o-120o and F: 20o-0o-70o mennjadi T6: S: 70o-0o-132o, F: 50o-0o-130o. Conclusion: physiotherapy modalities infra red rays can reduce pain in the shoulder region in conditions Clavicula dektra fracture, exercise therapy in the form of passive exercise, active exercise and hold relax can maintain range of motion and maintain muscle strength at the fracture condition Clavicula dektra with mounting plate and screws.